The concept of acquired knowledge ("Ilm Al-Husuli and its reformation in the discourse of some of the Muslim scholars) - Mohd Amin, Wan Mohd Azam (s.n, 2012)
This paper examines the concept of acquired knowledge ('Ilm al-husuli) in the discourse of Muslim scholars and its relation to the effort of its reformation made by many Muslim scholars and thinkers such as al-Shafi, al-Ghazali and al-Dihlawi. Al-Shafi'i contributes much efforts in this field as he classified knowledge into two categories, ilm al-sina'ah (crafs) in the acquired knowledge which branches out 'ilm al-hikmiyyah al-aqliyyah (rational science) and ilm al-naqliyyah al-wad'iyyah (traditional transmitted sciences).